2017 IEEE/ACM 21st International Symposium on Distributed Simulation and Real Time Applications (DS-RT) 2017
DOI: 10.1109/distra.2017.8167677
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically distributed network control for message dissemination in ITS

Abstract: We propose D2-ITS, a flexible and extensible framework to dynamically distribute network control to enable message dissemination in Intelligent Transport Systems (ITS). By decoupling the control-from the data plane, D2-ITS leverages network programmability to address ITS scalability, delay intolerance and decentralization. It uses a distributed control plane based on a hierarchy of controllers that can dynamically adjust to environment-and network conditions in order to satisfy ITS application requirements. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…As previously pointed out, in [8], we propose D2-ITS, a novel dynamically distributed network control plane framework and show how it is able to support ITS' Road Hazard Warning (RHW) message dissemination application.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously pointed out, in [8], we propose D2-ITS, a novel dynamically distributed network control plane framework and show how it is able to support ITS' Road Hazard Warning (RHW) message dissemination application.…”
Section: Related Workmentioning
confidence: 99%
“…In [8], we demonstrated that by decoupling the controlfrom the data plane, D2-ITS leverages network programmability to address ITS scalability, delay intolerance and decentralization. In this work, we extend D2-ITS with handover and load balancing capabilities in order maintain continuous service availability and satisfy application quality-of-service requirements when subject to conditions such as unpredictable mobility patterns of fast moving vehicles, communication channel impairments, etc.…”
Section: D2-its Handover and Load Balancingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the applications considered in our work are commercial or entertainment related, while the safety or emergency related services are not addressed by our protocol in view of their high reliability and time constraint requirements. Actually, for those safety-related applications, the most feasible solution is direct broadcasting, including CAM (Cooperative Awareness Messaging), DENM (Decentralized Environmental Notification Messaging) and BSM (Basic Safety Messaging) etc [4].…”
mentioning
confidence: 99%